USING HERRINGBONE AND SQ4R TECHNIQUES TO IMPROVE STUDENTS' ENGLISH READING COMPREHENSION THROUGH TEACHING AND LEARNING OF ENGLISH AT SMK NEGERI 1 MAKASAR - Lisna Wati; Kisman Salija; Munir Munir (State University of Makassar, 2023)
This study's purpose was to find out how the Herringbone and SQ4R techniques could be used to help SMK students' reading comprehension. Quantitative experimental research methods and quasi-experimental research methods are used in this study. Students in class XI at SMK Negeri 1 Makassar during the odd semester of the academic year 2022/2023 made up the population in this study. For the purpose of evaluating how the Herringbone and SQ4R approaches affect students' English reading comprehension, the population was chosen at random. The pre-test, treatment, and post-test are the study's instruments. The Herringbone Technique was effective in enhancing the reading comprehension of students based on data analysis outcomes and computation. This is evident from the findings that the post-treatment average student scores fell into the